2014
DOI: 10.1016/j.ejrad.2014.05.019
|View full text |Cite
|
Sign up to set email alerts
|

Dual-phase CT findings of groove pancreatitis

Abstract: Purpose Groove pancreatitis is a rare focal form of chronic pancreatitis that occurs in the pancreaticoduodenal groove between the major and minor papillae, duodenum and pancreatic head. Radiologic appearance and clinical presentation can result in suspicion of malignancy rendering pancreaticoduodenectomy inevitable. This study reports dual phase CT findings in a series of 12 patients with pathology proven groove pancreatitis. Materials and methods Retrospective review of preoperative CT findings in 12 patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 19 publications
0
27
0
1
Order By: Relevance
“…[ 30 ] More recently, Zaheer et al , reported pancreatic duct dilatation in 8 of their 12 patients (66.66%), calcifications localized to the head in 4 (33%), diffuse calcification in 1 (8.33%), and pancreatic glandular atrophy in 3 (25%) patients. [ 31 ] Twelve of our 33 (36.3%) patients showed pancreatic parenchymal atrophy, while 10 (30.3%) patients showed pancreatic calcifications and as many as 18 (54.54%) patients showed main pancreatic duct dilatation.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…[ 30 ] More recently, Zaheer et al , reported pancreatic duct dilatation in 8 of their 12 patients (66.66%), calcifications localized to the head in 4 (33%), diffuse calcification in 1 (8.33%), and pancreatic glandular atrophy in 3 (25%) patients. [ 31 ] Twelve of our 33 (36.3%) patients showed pancreatic parenchymal atrophy, while 10 (30.3%) patients showed pancreatic calcifications and as many as 18 (54.54%) patients showed main pancreatic duct dilatation.…”
Section: Discussionmentioning
confidence: 89%
“…[ 24 28 ] The pure form of the disease is relatively uncommon; in a surgical series of 600 patients, the pure form was detected in only 2% cases, although the changes in the pancreatic head may not always identifiable on imaging alone. [ 9 31 ]…”
Section: Discussionmentioning
confidence: 99%
“…However, we would like to acquaint the readership with other terminologies that are used synonymously to describe groove pancreatitis including paraduodenal pancreatitis, cystic duodenal dystrophy, duodenal pancreatitis, etc. [2,3]. Of these, paraduodenal pancreatitis needs a distinct mention.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%
“…PET/CT is relevant for the imaging of thymic tumors but it is expensive, includes high doses of radiation exposure, and is not readily available [2]. In fact, DWI could be used for the diagnosis of a tumor as well as aggressiveness of a lesion.…”
mentioning
confidence: 99%
See 1 more Smart Citation